If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n + 3(7n + -1) = -3 + 2n Reorder the terms: 8n + 3(-1 + 7n) = -3 + 2n 8n + (-1 * 3 + 7n * 3) = -3 + 2n 8n + (-3 + 21n) = -3 + 2n Reorder the terms: -3 + 8n + 21n = -3 + 2n Combine like terms: 8n + 21n = 29n -3 + 29n = -3 + 2n Add '3' to each side of the equation. -3 + 3 + 29n = -3 + 3 + 2n Combine like terms: -3 + 3 = 0 0 + 29n = -3 + 3 + 2n 29n = -3 + 3 + 2n Combine like terms: -3 + 3 = 0 29n = 0 + 2n 29n = 2n Solving 29n = 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 29n + -2n = 2n + -2n Combine like terms: 29n + -2n = 27n 27n = 2n + -2n Combine like terms: 2n + -2n = 0 27n = 0 Divide each side by '27'. n = 0 Simplifying n = 0
| 18=6+4 | | 7(4y-9)-(8y+8)= | | .25+12=2+x | | 2(8-6x)+1=-3-37 | | -35+o=98 | | -6(2-r)=42 | | y-1.9=5.59 | | 10m-8+2=7m+12 | | 50s+400=2000 | | 50s+400=650 | | p-(-24)=35 | | 4(d+723)=876 | | X^2+14x-68=7 | | Z^2=Q^2 | | 231=14+31y | | f+5=34 | | 7-j/3=25 | | 26-3a=6(1+a)+a | | 5(w+7)=65 | | 4a-3=-x-5 | | 2.1/12.6 | | 3n/15n | | -4(1-5v)=8v-40 | | 4x+3.4x-2x=4x | | 10y+8=4 | | 8y+4=10 | | 1-2n=1-3n | | ^3/^7 | | 4y+8=10 | | 4s+20=20 | | 54=9(T-91) | | 6n-(5n+6)=-2+3n |